Offshore wind farm disturbance alters ecological thresholds and reshapes niche distribution patterns of nekton communities: Insights from indicator species - Danyi Ke; Wanhong Han; Shuting Jia; Shuyuan Huang; Shiya Huang; Xiaobo Wang; Qingxi Han (Marine Pollution Bulletin, 2026)

Integrated biological sulfidogenic process: Synergizing sulfate and elemental sulfur reduction for metal-laden wastewater treatment - Jiahua Guo; Junjie Han; Chenxin Zhang; Hao Li; Cheng Li; Shuting Chen; Yibo Wang; Yu Li; Feng Jiang (Water Research, 2026)

Investigating the risk mechanisms underlying community diversity in the offshore wind farm through nonlinear threshold responses of zooplankton indicator species - Shuting Jia; Wanhong Han; Shuyuan Huang; Haodong Liu; Xiaobo Wang; Qingxi Han (Marine Environmental Research, 2026)

Rethinking Ship Emission Hotspots: A 100 m Resolution AIS-Based Inventory for Coastal Chinese Waters - Shuting Sun; Huihui Zhao; Xianchao Yang; Li Zhu; Wei Han (Journal of Marine Science and Engineering, 2026)
Existing ship emission inventories for coastal seas are typically gridded at 500 m to 1 km, a resolution too coarse to distinguish navigation channels from anchorage zones. Whether the hotspot patterns reported at such scales reflect true emission geography or are artifacts of spatial averaging remains an open question. We construct a 100 m resolution AIS-based emission inventory for two contrasting coastal environments in eastern China—the Yangtze River estuary and the Wenzhou coastal area—using the STEAM framework, and we quantify spatial concentration with Lorenz curve analyses. At this finer resolution, three emission archetypes become separable: discrete anchorage clusters, bankside berthing bands flanking navigation lanes, and sinuous riverbank traces in confined waterways. Emissions are extremely concentrated: the top 1% of grid cells capture over three-quarters of the total theoretical emission potential (Gini = 0.940), and this pattern persists across all months of 2023. Reaggregating the same data to 1 km reduces the top-1% share by roughly 10%, confirming that coarse gridding systematically understates anchorage contributions while overstating those of transit corridors. A dedicated sensitivity analysis on auxiliary engine load assumptions (±30% perturbation of canonical Jalkanen-style load brackets) shows that, while absolute emission totals carry approximately ±15% uncertainty, the spatial concentration of emissions is highly robust: Across all perturbation scenarios, the Gini coefficient varies by less than 0.01, the top-5% emission share varies by less than 2 percentage points, and the location of top-5% hotspot cells overlaps by ≥97.9% (Jaccard index). The results highlight stationary vessel hotspots—discrete anchorages and bankside berths—as a major and previously underemphasized contributor to the cumulative coastal ship emission budget, complementing rather than replacing the conventional navigation-lane focus, with direct implications for shore power siting, anchorage management, and emission control zone design.

Myasthenia Gravis patients have reduced DTI-ALPS-Index and gBOLD-CSF coupling, suggesting impaired brain waste clearance - Jianxian Zeng; Shuting Han; Mengying Zhu; Yi Shang; Peng Wu; Qinghua Gu; Yonggang Li (Brain Imaging and Behavior, 2026)

Paleoglacial coverage and paleoclimatic reconstruction of MIS 3b and the gLGM in the Turgen–Asgat Catchment, Altai Mountains - Chang Liu; Liang Liu; Yijie Zhai; Shuting Han; Zheng Yang; Wei Zhang (Journal of Earth System Science, 2026)

Cadmium immobilization and selenium mobilization by Citrobacter freundii in soil-rice system: a trade-off between remediation efficacy and soil microbial community integrity - Fuyu GUO; Tianao YU; Rui ZHANG; Tingting CHU; Meng ZHU; Shuting ZAN; Fengxiang X. HAN; Ruyi YANG (Pedosphere, 2026)

Theoretical, experimental and numerical study on mechanical properties of innovative PSRC floor - Wenkang Wang; Shuting Liang; Xiaojun Zhu; Jian Yang; Tiancheng Han; Yiwei Xu; Yinjie Lu (Engineering Structures, 2025)

Experimental study on the flexural behavior of large-span prestressed and steel-reinforced concrete slabs - Tiancheng Han; Shuting Liang; Xiaojun Zhu; Wenkang Wang; Jian Yang (Engineering Structures, 2025)

A high-performance wearable microneedle sensor based on CNT/CCNT@Cu-ZIF-67 composites for simultaneous detection of uric acid and dopamine - Jiachen Zhu; Weiliang Wang; Luwen Wang; SongYa Cui; Dongxue Han; Shuting Liu; Shaopeng Ma; Shangbin Xi; Wei Cai; Liang Peng (Chemical Engineering Journal, 2025)

KOH-modified biochar enhances nitrogen metabolism of the chloroquine phosphate-disturbed anammox: Physical binding, EPS modulation and versatile metabolic hierarchy - Rui Hu; Xue Chen; Yule Han; Wanjiang Li; Shuting Zhang; Zhaobin Liu; Jiandong Wang; Xueqin Lu; Gang Luo; Shicheng Zhang; Guangyin Zhen (Journal of Hazardous Materials, 2025)

Fetal weight growth trajectories and childhood development: A population-based cohort study - Xinmei Chen; Hongxiu Liu; Aifen Zhou; Feng Jin; Chufeng Jing; Yuanyuan Li; Wei Xia; Linda G. Kahn; Ya Xie; Xingliang Xiang; Shuting Cao; Wenxin Zhang; et al. (Science Bulletin, 2024)

Retrieval of cloudy land surface temperature from AMSR2 brightness temperature, precipitable water vapour and cloud liquid water - Cheng Huang; Shuting Zhang; Wenjing Han; Xiyue Feng; Si-Bo Duan (International Journal of Remote Sensing, 2024)

Seasonal changes in the phenolic compound contents and bioactivities in Betula platyphylla bark determined by soil properties - Quanxing Dong; Junrui Han; Shuang Wu; Yulin Pang; Yuwen Chen; Qianru Ji; Shengfang Wang; Shuting Zhao; Guanchao Cheng; Cholil Yun; Wenjie Wang; Huimei Wang (Flora, 2024)

Suppressing the Jahn–Teller effect in Mn-based Prussian blue analogues by linear (N O) anions - Qinghao Han; Zonghua Yang; Ya’nan Hu; Shuting Gao; Xingjun Liu; Cuiping Wang; Jiajia Han (Chemical Engineering Journal, 2024)

Preparation of a novel Ti/TNAs/PbO2-PVDF-Er2O3 anode by Ti3+ self-doping TNAs and its electrocatalytic performance for hydroquinone degradation - Linxia Li; Wei Zhu; Huixi Li; Shuting Li; Lei Han; Lian Ren; Meng Wang; Xia Lu; Jiali Yuan; Shutong Li; Yize Wu; Zhen Chen; et al. (Journal of Environmental Chemical Engineering, 2023)

Coupling effect analysis of drip irrigation and mixed slow-release nitrogen fertilizer on yield and physiological characteristics of winter wheat in Guanzhong area - Xin Wang; Youzhen Xiang; Jinjin Guo; Zijun Tang; Shuting Zhao; Han Wang; Zhijun Li; Fucang Zhang (Field Crops Research, 2023)

Free nitrous acid-assisted asymmetrical alternating current electrochemistry (FNA-AACE) for multi-heavy metals decontamination in waste activated sludge - Zhibo Han; Yili Wang; Daxin Zhang; Xiaoyang Fan; Shuting Zhang; Meilin Liu (Water Research, 2023)

Synthesis of nano-Fe3O4/ZnO composites with enhanced antibacterial properties and plant growth promotion via one-pot reaction - Xiaohui Ji; Yuanyuan Han; Yinghua Wu; Ben Liang; Jinli Zheng; Shuting Ma; Chen Li; Haitao Xu; Shaobo Guo (Environmental Science and Pollution Research, 2023)

Ectopic expression of grape hyacinth R3 MYB repressor MaMYBx affects anthocyanin and proanthocyanidin biosynthesis and epidermal cell differentiation in Arabidopsis - Jiangyu Wang; Boxiao Zhang; Shuting Tian; Han Zhang; Jiaxin Gong; Kaili Chen; Lingjuan Du (Horticulture, Environment, and Biotechnology, 2022)

A New DIC-Based Method to Identify the Crack Mechanism and Applications in Fracture Analysis of Red Sandstone Containing a Single Flaw - Shuting Miao; Peng-Zhi Pan; Shankun Zhao; Jun Han; Petr Konicek (Rock Mechanics and Rock Engineering, 2021)

Determining the contributions of climate change and human activities to the vegetation NPP dynamics in the Qinghai-Tibet Plateau, China, from 2000 to 2015 - Bing Guo; Baomin Han; Fei Yang; Shuting Chen; Yue Liu; Wenna Yang (Environmental Monitoring and Assessment, 2020)

Study and Application of the Interaction Between Asymmetrical Porphyrin and Ascorbic Acid - Shuting Sun; Dan Wu; Qin Wei; Yanyan Han; Xin Chen; Yunxia Shen; Peihua Zhu; Bin Du (Journal of Fluorescence, 2009)